Modeling of vapor-liquid interactions in condensing ejectors. (April 2022) - Wang, Nanqiao; Bhushan, Shanti; Cho, Heejin; Li, Like
Highlights: A 1D slug-flow model for condensing ejectors was presented. The model can simulate ejectors with both primary vapor and primary liquid flows. The model was validated with experiments reported in the literature. A parametric study was conducted to examine the ejector performance. The interfacial heat transfer coefficient has the most significant effect. Abstract: Ejectors are compact mechanical devices that utilize the expansion of a high-pressure primary fluid to entrain and compress a low-pressure secondary fluid by means of momentum transfer between the two streams of fluid. Condensing ejectors feature both momentum and heat transfer through the interaction between the vapor and liquid streams. The goal of this paper is to develop and validate a one-dimensional slug flow model to simulate the vapor–liquid interactions in two types of condensing ejectors – one with primary liquid and secondary vapor flows (Type I), and the other with primary vapor and secondary liquid flows (Type II). Control volume analysis of the mass, momentum, and energy balance in each phase and across the interface was conducted for the ejectors. The slug flow models for both types of ejectors are validated with published results in the literature. The friction coefficient on the inner wall of the ejectors and the interfacial heat transfer coefficient are identified as controlling parameters for the ejector performance in terms of pressure and temperature distributions along the axis. The detailed parametric study shows that the liquid inlet velocity and mixing tube diameter have a significant impact on the performance of the Type I ejectors, and the performance of the Type II ejectors is mainly controlled by the secondary liquid flow inlet temperature.